INFLUENCE OF CAREER DEVELOPMENT, WORK ENVIRONMENT, COMPENSATION AND IT’S IMPLICATION ON JOB SATISFACTION OF PERMANENT LECTURER AT MARITIME COLLEGES IN DKI JAKARTA - Muktar Sitompul, Ali; Marhalinda, Marhalinda; Moeins, Anoesyirwan (Dinasti International Journal of Economics, Finance & Accounting, 2020)
This study aims to analyze and prove the Influence Career Development, Work Environment, Compensation and it’s implication on job satisfaction of permanent lecturer of maritime colleges in DKI Jakarta both partially and simultaneously. The research method used is descriptive survey method and explanatory survey with 253 respondents. The analysis of the data used is Structural Equation Modeling (SEM), consisting of career development, work environment and compensation as exogenous variables, job satisfaction as an endogenous variable. Based on the partially and simultaneous research that Career development, work environment and compensation have a positive and significant effect on job satisfaction with a contribution (R2) of 92 %. Work environment has the most dominantt effect on the job satisfaction of lecturers at maritime colleges in DKI Jakarta.